Invention into the AC Voltage Regulator with V/F Technique for Induction Motor Starting Applications - Mahesh Kollipara; V N Srinivasa Rao Kolluru (Institute of Advanced Engineering and Science, 2015)
Modern electrical motors are available in many different forms with different mounting arrangements. To ensure a long life for the motor it is important to select it with correct degree of protection when operating under heavy duty conditions in a severe environment. Smooth starting is also one of major considerations to get long life and optimum efficiency. The conventional method to start an asynchronous motor with a soft starter is by reducing the voltage of the motor by varying the voltage “off time”. The “off time” could for example be controlled to achieve a desired maximum current level or a constant driving torque. Even if the voltage is reduced the fundamental frequency of the voltage is equal to the supply voltage frequency. That gives a large difference between angular speed of supply voltage and angular speed of the rotor during start. Due to the large difference in angular speed the motor flux will be low and thereby also the ability to produce torque. Instead of using the conventional control method with a reduced voltage it is possible to use a method with controlled flux similar to frequency inverters for soft-starters. As the soft-starter does not have the intermediate DC energy storage the applied voltage vector has to be directly modulated from the mains supply.